Black fatigue : how racism erodes the mind, body, and spirit - Winters, Mary-Frances (Berrett-Koehler Publishers, Inc., 2020)
This is the first book to define and explore Black fatigue, the intergenerational impact of systemic racism on the physical and psychological health of Black people--and explain why and how society needs to collectively do more to combat its pernicious effects. Black people, young and old, are fatigued, says award-winning diversity and inclusion leader Mary-Frances Winters. It is physically, mentally, and emotionally draining to continue to experience inequities and even atrocities, day after day, when justice is a God-given and legislated right. And it is exhausting to have to constantly explain this to white people, even--and especially--well-meaning white people, who fall prey to white fragility and too often are unwittingly complicit in upholding the very systems they say they want dismantled. This book, designed to illuminate the myriad dire consequences of "living while Black, "came at the urging of Winters's Black friends and colleagues. Winters describes how in every aspect of life--from economics to education, work, criminal justice, and, very importantly, health outcomes--for the most part, the trajectory for Black people is not improving. It is paradoxical that, with all the attention focused over the last fifty years on social justice and diversity and inclusion, little progress has been made in actualizing the vision of an equitable society. Black people are quite literally sick and tired of being sick and tired. Winters writes that "my hope for this book is that it will provide a comprehensive summary of the consequences of Black fatigue, and awaken activism in those who care about equity and justice--those who care that intergenerational fatigue is tearing at the very core of a whole race of people who are simply asking for what they deserve."